Benefits and Challenges of Implementing Green Initiatives at Public Universities in South Africa - Bisschoff, Christo; Tshivshe, Lelo (Journal of Economic Development, Environment and People, 2023)
This article explores the benefits and challenges of implementing green initiatives at South African Universities. The study's objectives are to identify the benefits and to find ways to overcome the challenges preventing green initiative implementation. In a mixed-method approach, eight senior personnel at prominent South African universities were interviewed to identify specific green initiatives and suitable measuring criteria. A five-point Likert scale questionnaire was distributed online to other university managers and senior staff. A total of 144 personnel members completed the questionnaire. The results show that the data are reliable (α=0.843), adequate (KMO=0.641), and significant (p≤0.05 at the 95% confidence level. The respondents perceive the barriers to implementing green initiatives at public universities to be significant (≥4.5) and indicate that universities are progressing excellently with implementing some green initiatives (for example, by eliminating paper usage, electronic signing of documents, LED lighting, and paperless IT system applications) (≥4.5). The benefits of green implementation are also significant (≥4.5). Exploratory factor analysis identified three factors each for barriers, implementation, and benefits, explaining a cumulative variance of 56.1%, 82.2% and 54.8%, respectively. Public universities' management can operationalise the results in their green initiatives implementation strategies.